NEW SPECIES OF LABISIA (MYRSINACEAE) FROM SUMATRA - Sunarno, Bambang - (REINWARDTIA, 2002)
Â SUNARNO, BAMBANG. 2002. New species of Labisia (Myrsinaceae) From Sumatra. Reinwardtia 12(1): 121â 124. ? Three new species L. posthumusiana, L. steenisiana and L. sumatrensis are described.